Marnazar Tradition: The Valuse of Islamic Education on The Local Wisdom of The Community - Nasution, Karnada; Ulfah, Maria; Tanjung, Ramadan (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
At the beginning of the farming season, people in Bonan Dolok village make vows (promises) by carrying out the marnazar tradition. The Marnazar tradition is a medium and forum for the community to express gratitude to Allah SWT for the harvest obtained. This paper aims to examine the values of Islamic education from the local wisdom of the Bonan Dolok village community. In the discussion, it will be described about the history and implementation of the marnazar tradition and what Islamic educational values are contained in it. The research used a qualitative approach with the background of activities, namely the marnazar tradition in Bonan Dolok village. The results of the study showed that there are values of Islamic education in the marnazar tardisi which broadly include the value of creed education and the value of moral education. 1) the value of creed education, making Allah Almighty a place to ask for help and pray. 2) the value of moral education, including; The value of almsgiving, the value of friendship and the value of helping help.